Analysis of the Effects of Polarity Variations, Electrode Types, and Cooling Media on the Tensile Strength of ASTM A36 Steel Welded Joints: Analisa Pengaruh Variasi Polaritas, Elektroda, dan Media Pendingin Terhadap Kekuatan Tarik Sambungan Las Material Baja ASTM A36 - Anis Siti Nurrohkayati; Zakki Anggara (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the pivotal role of welding in manufacturing and construction, specifically in the context of material joining for ASTM A36 steel. The study aims to determine the impact of polarity, electrode type, and coolant on the maximum tensile strength of welds. A total of 54 specimens were welded using Shielded Metal Arc Welding (SMAW) with DCEN and DCEP polarities, employing electrode variations of E6013, E7016, and E7018, along with different coolants—Air, Oil, and Saltwater. The results reveal that E7018 welding at a speed of 100 mm/s exhibited the highest tensile strength of 529 MPa, with an average maximum load of 37.35 kN. Conversely, the lowest tensile strength was observed in E6013 welding at 100 mm/s, recording 339 MPa with an average maximum load of 25.84 kN. Additionally, E7018 welding at a speed of 100 mm/60 s showed the highest elasticity of 22.08% with a maximum load of 37.55 kN. These findings contribute valuable insights for optimizing welding processes, thereby enhancing the mechanical integrity of ASTM A36 steel in various industrial applications. Highlights: Significance of Polarity: Investigating the impact of DCEN and DCEP polarities on welded material strength. Electrode Influence: Understanding how E6013, E7016, and E7018 electrodes affect the mechanical properties of welds. Coolant Consideration: Analyzing the role of Air, Oil, and Saltwater as coolants in optimizing welding outcomes. Keywords: Welding, ASTM A36 steel, Polarity, Electrode, Coolant